2021
DOI: 10.1111/hex.13391
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of coproduction to better understand the barriers to achieving sustainability in NHS chronic kidney services and create alternate pathways

Abstract: Context Too many people living with chronic kidney disease are opting for and starting on hospital‐based dialysis compared to a home‐based kidney replacement therapy. Dialysis services are becoming financially unsustainable. Objective This study aimed to assess the efficacy of coproductive research in chronic kidney disease service improvement to achieve greater sustainability. Design A 2‐year coproductive service improvement study was conducted with multiple stakeholders with the specific intention of maximiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The British National Health Service is increasingly integrating coproduction approaches into its health system-including but not limited to the mental health system-and could serve as a model. [96][97][98][99][100] Finally, social policy changes are critical to improving population mental health moving forward. 75 Specifically, the relationship between oppression and poor mental health points to the imperative to dismantle public policies that perpetuate oppression, such as mandatory minimum sentencing policies and funding of public education via property taxes.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…The British National Health Service is increasingly integrating coproduction approaches into its health system-including but not limited to the mental health system-and could serve as a model. [96][97][98][99][100] Finally, social policy changes are critical to improving population mental health moving forward. 75 Specifically, the relationship between oppression and poor mental health points to the imperative to dismantle public policies that perpetuate oppression, such as mandatory minimum sentencing policies and funding of public education via property taxes.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…5 More optimistically, however, there is emerging evidence to suggest successful change management following a renewed emphasis on PPIE: McLaughlin et al observed the importance of coproduction in improving chronic kidney disease care pathways in the NHS, while O'Flaherty et al also advocate for stakeholder engagement in evaluating the effectiveness of the NHS Health Check programme. 6,7 The implementation gap A key limitation when applying a systems approach to QI in healthcare has been to transition from a purely theoretical exercise towards real-world applicability. Despite being comprehensive in its scope, the approach is grounded in complexity and poses questions of resources, training and appetite.…”
Section: Benefitsmentioning
confidence: 99%
“…22 Barriers to home dialysis have been found to be complex. 23 Patients have reported insufficient knowledge and education as a barrier to selecting home dialysis. 24 Practically, home dialysis requires people to have adequate housing including space for supplies and in the case of home haemodialysis (HHD), an affordable and satisfactory supply of water.…”
Section: Open Accessmentioning
confidence: 99%
“…Elsewhere, we report the outcomes from the coproduction in relation to specific service improvement aspects of the study. 23 In this paper, we include the patient and public involvement (PPI) and wider stakeholder activity related to the empirical research study. We map the PPI in the study against the UK standards for public involvement 38 Open access online file (online supplemental appendix 2).…”
Section: Patient Public and Stakeholder Involvementmentioning
confidence: 99%